Cultural Ethnography of Pecel Madiun: Reconceptualizing Civic Spaces for National Character Formation - Yoga Ardian Feriandi; Risti Aulia Ulfah; Ary Purwatiningsih (Institut Agama Islam Negeri Ponorogo, 2026)
This study aims to analyze the role of traditional cuisine as a medium for lived citizenship in the formation of national character. Utilizing a qualitative approach with a focused ethnography design, this research was conducted at warung pecel (traditional food stalls) in Madiun City from December 2025 to January 2026. Data were gathered through focused observation, in-depth interviews, and visual documentation, which were then analyzed inductively through the lenses of the sociology of citizenship and public space. The results indicate that warung pecel functions as an egalitarian and inclusive civic space imbued with citizenship values. Social practices such as communal seating regardless of social class, the ethics of